Analisis Yuridis Terhadap Tingkat Efisiensi Penyelesaian Perselisihan Hasil Pemilukada oleh MK - Khastama, Iqbal; Wardana, Dodi Jaya (Universitas Ekasakti, 2023)
The results of votes obtained in official legislative elections by the KPU often receive unsatisfactory responses from election participants. This was triggered by intent, negligence, technical errors, administrative weaknesses or human error. In order to realize democratic elections, the following principles should be applied; honest; independent; orderly, fair, legal certainty; prioritizing public interests; openness and transparency; proportionality; professionalism; accountability; efficiency; and effectiveness. The Constitutional Court should have credibility and professionalism as a decision maker in election disputes. In 2019, 676 PHPU cases were reported to the Constitutional Court and 1135 other cases related to Kada PHP. UU no. 7 of 2017